Stop Bullying Sebagai Upaya Pencegahan Perilaku Perundungan Di Lingkungan Sekolah - Pulungan, Silfa Hafizah; Fitriana Pul, Winda; Hasibuan, Maulidin Gufron; Hasibuan, Riski Syafutra; Hasibuan, Nur Habibah (Lembaga Einstein College, 2025)
Bullying is repeated aggressive behavior intended to hurt, humiliate, or dominate others emotionally, physically, or mentally. The goal of this activity is to raise students' awareness of the negative effects of bullying and encourage them to play an active role in preventing it and creating a bullying-free school environment. This activity involves presenting material about bullying to students in the classroom, followed by a question-and-answer session with the presenter. This presentation and Q&A session are expected to increase students' understanding, preventing them from becoming perpetrators or victims of bullying. This will have a positive impact and help create a bullying-free environment in schools and homes